In-hospital care, complications, and 4-month mortality following a hip or proximal femur fracture: the Spanish registry of osteoporotic femur fractures prospective cohort study - Prieto-Alhambra, Daniel (Arch Osteoporos, 2018)
SUMMARY: We have characterised 997 hip fracture patients from a representative 45 Spanish hospitals, and followed them up prospectively for up to 4 months. Despite suboptimal surgical delays (average 59.1 hours), in-hospital mortality was lower than in Northern European cohorts. The secondary fracture prevention gap is unacceptably high at 85%. PURPOSE: To characterise inpatient care, complications, and 4-month mortality following a hip or proximal femur fracture in Spain. METHODS: Design: prospective cohort study. Consecutive sample of patients ≥ 50 years old admitted in a representative 45 hospitals for a hip or proximal femur fragility fracture, from June 2014 to June 2016 and followed up for 4 months post-fracture. Patient characteristics, site of fracture, in-patient care (including secondary fracture prevention) and complications, and 4-month mortality are described. RESULTS: A total of 997 subjects (765 women) of mean (standard deviation) age 83.6 (8.4) years were included. Previous history of fracture/s (36.9%) and falls (43%) were common, and 10-year FRAX-estimated major and hip fracture risks were 15.2% (9.0%) and 8.5% (7.6%) respectively. Inter-trochanteric (44.6%) and displaced intra-capsular (28.0%) were the most common fracture sites, and fixation with short intramedullary nail (38.6%) with spinal anaesthesia (75.5%) the most common procedures. Surgery and rehabilitation were initiated within a mean 59.1 (56.7) and 61.9 (55.1) hours respectively, and average length of stay was 11.5 (9.3) days. Antithrombotic and antibiotic prophylaxis were given to 99.8% and 98.2% respectively, whilst only 12.4% received secondary fracture prevention at discharge. Common complications included delirium (36.1 %) and kidney failure (14.1%), with in-hospital and 4-month mortality of 2.1% and 11% respectively. CONCLUSIONS: Despite suboptimal surgical delay, post-hip fracture mortality is low in Spanish hospitals. The secondary fracture prevention gap is unacceptably high at > 85%, in spite of virtually universal anti-thrombotic and antibiotic prophylaxis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11657-018-0515-8) contains supplementary material, which is available to authorized users.